The Curriculum Management in Madrasah Diniyyah Assirajiyah, Menur Mranggen Demak - Hanifuddin, Hanifuddin; Fakhruddin, Fakhruddin; Yusuf, Amin (Educational Management, 2021)
Religious education aims to educate students with the understanding and practice of the values of religious teaching and is based on noble characters (ahlaqul karimah). The values of religious teachings and characters are part of character education which now has become an inevitability in the implementation of education. Madrasah diniyyah has become one of the important pillars and has had an undeniable role in carrying out religious education. The dynamics of social development and educational innovation are a challenge for the existence of madrasah diniyyah, one of which is in the field of curriculum management. It is absolutely that curriculum management is a necessity for Madrasah diniyyah to be able to respond to the demands and challenges of social dynamics. The purpose of this study is to analyze the planning, organization, implementation, supervision, and evaluation of curriculum in Madrasah Diniyyah. The method used was a qualitative approach with a case study design. Moreover, the data obtained through the interview, observation, and document study. The results showed that the curriculum planning of Madrasah Diniyyah referred to the vision and stipulation of the FKDT (Diniyyah Takmiliyyah Communication Forum) which was aligned with the social condition. The composition of the curriculum is divided into three forms, namely learning activities, cultural art skills, and practicing religious values. The curriculum of madrasah diniyyah was implemented in the classroom in the form of learning, and outside the classroom in the form of guidance and skills activities. The supervision and evaluation of the curriculum were carried out by the supervisor and principal of madrasah diniyyah regularly.